In vitro Activity of Antimicrobial Wound Dressings on P. aeruginosa Wound Biofilm - Stuermer, Ewa Klara; Plattfaut, Isabell; Dietrich, Michael; Brill, Florian; Kampe, Andreas; Wiencke, Vanessa; Ulatowski, Anna; Geffken, Maria; Rembe, Julian-Dario; Naumova, Ella Alexandrovna; Debus, Sebastian Eike; Smeets, Ralf (Frontiers in Microbiology, 2021)
The treatment of acute and chronic infected wounds with residing biofilm still poses a major challenge in medical care. Interactions of antimicrobial dressings with bacterial load, biofilm matrix and the overall protein-rich wound microenvironment remain insufficiently studied. This analysis aimed to extend the investigation on the efficacy of a variety of antimicrobial dressings using an in-vitro biofilm model (lhBIOM) mimicking the specific biofilm-environment in human wounds. Four wound dressings containing polyhexanide (PHMB), octendine di-hydrochloride (OCT), cadexomer-iodine (C-IOD) or ionic silver (AG) were compared regarding their antimicrobial efficacy. Quantitative analysis was performed using a quantitative suspension method, separately assessing remaining microbial counts within the solid biofilm as well as the dressing eluate (representing the absorbed wound exudate). Dressing performance was tested against P. aeruginosa biofilms over the course of 6 days. Scanning electron microscopy (SEM) was used to obtain qualitative visualisation on changes in biofilm structure. C-IOD demonstrated superior bacterial reduction. In comparison it was the only dressing achieving a significant reduction of more than 7 log10 steps within three days. Neither the OCT- nor the AG-containing dressing exerted a distinct and sustained antimicrobial effect. PHMB achieved a non-significant microbicidal effect (1.71±0.31 log10 steps) at day 1. Over the remaining course (6 days) it demonstrated a significant microbistatic effect compared to OCT, AG and the control. Quantitative results in the dressing eluate correlate with those of the solid biofilm model. Overall, AG- and OCT-containing dressings did not achieve the expected anti-biofilm efficacy, while C-IOD performed best. Chemical interaction with the biofilms extrapolymeric substance (EPS), visualized in the SEM, and dressing configuration (agent concentration and release pattern) are suspected to be responsible. The unexpected low and diverse results of the tested antimicrobial dressings indicate a necessity to rethink non-debridement anti-biofilm therapy. Focussing on the combination of biofilm-disruptive (for EPS structure) and antimicrobial (for residing microorganisms) features, as with C-IOD, using dehydration and iodine, appears reasonably complementary and an optimal solution, as suggested by the here presented in-vitro data.